2010
DOI: 10.1021/pr901130s
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Identifies Inflammatory and Noninflammatory Metabolic Effects of Genetic Modification in a Mouse Model of Crohn’s Disease

Abstract: Interleukin-10 is an immunosuppressive cytokine involved in the regulation of gastrointestinal mucosal immunity toward intestinal microbiota. Interleukin-10-deficient (IL10(-/-)) mice develop Crohn's disease-like colitis unless raised in germ-free conditions. Previous gas chromatography-mass spectrometry (GC-MS) metabolomic analysis revealed urinary metabolite differences between IL10(-/-) and wildtype C57BL/6 mice. To determine which of these differences were specifically associated with intestinal inflammati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 62 publications
3
63
2
Order By: Relevance
“…In another study on IL-10 gene deficient mice, Lin et al [17] showed an association between 15 metabolites including fucose, xanthurenic acid, and 5-aminovaleric acid with intestinal inflammation. Elevated urinary xanthu renic acid in gene deficient mice was linked to increased plasma levels of kynurenine [17] .…”
Section: Urinary Metabolomics In Ibdmentioning
confidence: 98%
See 2 more Smart Citations
“…In another study on IL-10 gene deficient mice, Lin et al [17] showed an association between 15 metabolites including fucose, xanthurenic acid, and 5-aminovaleric acid with intestinal inflammation. Elevated urinary xanthu renic acid in gene deficient mice was linked to increased plasma levels of kynurenine [17] .…”
Section: Urinary Metabolomics In Ibdmentioning
confidence: 98%
“…Elevated urinary xanthu renic acid in gene deficient mice was linked to increased plasma levels of kynurenine [17] . In a further study, the same group validated these findings by showing that feeding IL-10 gene-deficient and wild-type mice with Kiwifruit increases Kiwifruit-derived urinary metabolites more significantly in IL-10 genedeficient mice compared to wild-type mice without affecting urinary metabolites levels previously associated with inflammation [18] .…”
Section: Urinary Metabolomics In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven metabolites, including glutaric acid, 2-hydroxyglutaric acid and 2-hydroxyadipic acid, were significantly different in Il10 -/-compared with C57 mice, but these differences were not related to the severity of inflammation, and were possibly associated with the genetic manipulation that produced these animals, rather than any inflammatory-related function of IL-10. In contrast, fucose, xanthurenic acid and 5-aminovaleric acid were among fifteen metabolite differences associated with intestinal inflammation (Lin et al, 2010). The presence of defined metabolites associated with inflammation may be of benefit in enabling a non-invasive measurement of the severity of inflammation in human IBD.…”
Section: ) Mouse Modelmentioning
confidence: 99%
“…We have shown that food components such as polyunsaturated fatty acids (Knoch et al, 2009;Knoch et al, 2010) can prevent or ameliorate the level of intestinal inflammation, and have characterized changes in gene expression in association with this change in inflammation to better understand the mechanisms through which such food components might be acting. We have also used metabolomic analysis to measure urinary metabolite differences between Il10 -/-and wildtype C57BL/6 mice, and to determine which of these differences were associated with intestinal inflammation (Lin et al, 2010). Eleven metabolites, including glutaric acid, 2-hydroxyglutaric acid and 2-hydroxyadipic acid, were significantly different in Il10 -/-compared with C57 mice, but these differences were not related to the severity of inflammation, and were possibly associated with the genetic manipulation that produced these animals, rather than any inflammatory-related function of IL-10.…”
Section: ) Mouse Modelmentioning
confidence: 99%